A glimpse of the long view: Human attitudes to an established population of Eurasian beaver (castor fiber) in the lowlands of south-east England - Oliveira, Sara; Buckley, Phil; Consorte-McCrea, Adriana (Frontiers in Conservation Science, 2023)
The Eurasian beaver (Castor fiber) is a native species to Britain that after being absent for 400 years has been restored to the English countryside. The first beavers were released into a reserve in Kent in 2001/02, making this one of the first beaver release areas in the UK. This paper examines attitudes towards beaver presence in the landscape as well as public perception of beaver benefits and impacts with respect to the environment and human society. The factors influencing social attitudes and support for beaver reintroduction, as well as the relationship between sociodemographic variables and attitudes, were also investigated. Inhabitants of Kent and its immediate surroundings were surveyed during June and July of 2020 (n=407) with a focus on three interest groups – environmentalists, farmers and the general public. Perceptions included mostly beneficial impacts on nature and biodiversity, whereas less positive impacts were associated with economics, agriculture and fisheries. In general, local attitudes towards beavers were positive, mainly sustained by feelings of liking this wildlife species and valuing their presence. People´s attitudes positively influence willingness to support the reintroduction of beavers. Twenty years after their initial release, results indicate broad support for the beaver reintroduction in Kent and people´s tolerance of beavers. The majority of respondents were in favour of nonintrusive management techniques to mitigate beavers’ undesirable impacts. These findings suggest the need to develop an optimal management strategy that incorporates public views and gives advice on the best approach to manage this wildlife species. This research provides theoretical and practical underpinning for beaver management and conservation in Britain.